Simultaneous Occurrence of Acute Myeloid Leukemia and Chronic Lymphocytic Leukemia: A Case Report - Stjepan Galić; Ozren Jakšić (Liječnički vjesnik, 2023)
Concurrent development of acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL) is very rare. We present a case of simultaneous CLL and AML in a patient with no prior exposure to cytotoxic agents or irradiation.